Docentes universitarios: una mirada desde la autoeficacia general y engagement laboral - Lozano Paz, Carmen Rosa (2015)
The present research seeks to understand how general self-efficacy and work engagement in professor of psychology at a particular University of metropolitan Lima's career is presented. To achieve this goal, interviews were conducted with seven professors: three females and four males. From the interviews we understand what personal factors have helped them in the exercise of their profession. And also, with what they find engaged. Finally, the conclusions which were reached is that teachers are self-efficacy because they assessed their abilities and their environment in order to achieve their respective goals. And we also found that are engaged with their work of teaching.